Watch my baby grow - Bhattacharya, Shaoni; Holmstrom, Radhika; Hall, Sally J.; Young, E. (Emma) (DK Publishing, 2015)
"By following the journey of one child and her family, Watch My Baby Grow looks at a baby's developing abilities, from birth, over the course of a year. In the light of new scientific knowledge, this book explores every area of a baby's progress, and provides a fascinating insight into what it's really like from a baby's point of view."--p. 4 of jacket.